Evaluation of In Vitro Inhibitory Activity of Rye-Buckwheat Ginger Cakes with Rutin on the Formation of Advanced Glycation End-Products (AGEs) - Przygodzka Małgorzata; Zieliński Henryk (Polish Journal of Food and Nutrition Sciences)
In this study, the relationship between the inhibitory effects of extracts from rye-buckwheat ginger cakes supplemented with low and high rutin dosage baked without or with dough fermentation step on the formation of fluorescent advanced glycation end-products (AGEs), and phenolic compounds, rutin, D-chiro-inositol and antioxidant capacity were addressed. The cakes were based on rye flour substituted by light buckwheat flour or flour from roasted buckwheat groats at 30% level, and were produced with or without dough fermentation step. The inhibitory effect against AGEs formation was studied in bovine serum albumin (BSA)-glucose and BSA-methylglyoxal (MGO) systems. The antioxidant capacity was measured by 2,2-diphenyl- -1-picrylhydrazyl (DPPH) and cyclic voltammetry (CV), rutin and D-chiro-inositol contents by HPLC and total phenolics (TPC) by spectrophotometric assays. The study showed the inhibitory effects of extracts from rye-buckwheat ginger cakes supplemented with low and high rutin dosage. The results of the inhibitory activity were highly correlated in two applied model systems. Enrichment of rye-buckwheat ginger cakes with rutin improved their antioxidant properties. The correlation studies showed that the inhibitory effects of rye-buckwheat ginger cakes produced with dough fermentation step and enhanced with rutin against formation of AGEs were highly correlated with TPC, rutin and D-chiro-inositol contents, and antioxidant capacity. Moreover, the effect of rutin enrichment was clearly seen in cakes obtained with dough fermentation step, even the inhibitory activity was slightly lower as compared to the cakes produced without dough fermentation.